Jozef Pilsudski : founding father of modern Poland - Zimmerman, Joshua D. (Harvard University Press, 2022)
"An authoritative biography of Jozef Pilsudski, a key figure in interwar Europe regarded as the founding hero of a pluralistic and democratic modern Poland. After the first elected president was assassinated, Pilsudski lost faith in Poles' commitment to democracy, led a military coup, and ruled as a strongman, leaving a complicated legacy"--